The Relationship between Levels of Serum Vit. D and Kidney Function in Diabetic Nephropathy Iraqi Patient - Mijbel, Nadia A.; Ibrahim, Shafa J. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: According to several animal and human studies, Vitamin D appears to play a substantial role in the development of diabetic nephropathy, However, the possibility of vitamin D's renoprotective impact and influence on the reversal of already-existing renal damage remains speculative. Vitamin D deficiency and insufficiency are ubiquitous worldwide and have been linked to a variety of pathophysiological conditions, including diabetes, allergies, autoimmune illnesses, pregnancy difficulties, and, more recently, worse COVID-19 clinical outcomes. From a translational perspective, the goal of this review is to look into the potential function of vitamin D in the development of diabetic kidney disease.Objective: to evaluate the role of vit D on renal function in patient with DMT1.Patient and Method: The total number of study participants was 120, divided into three groups: Group A: Included 40 patients has DM with NP (stage1, stage 2, stage 3a), Group B included 40 patients had DM without NP, and group C included 40 healthy participants (control). Samples were taken from the Diabetic control clinic of Endocrinology and Diabetes center/Al-Kinde Hospital, Baghdad Teaching Hospital/ Medical City and Al-Shaheed Al- Sadder General Hospital during the period from October 2021 to March 2022. Result: Statistically significant weak positive correlations were detected between vitamin D and GFR (r= 0.321, P= 0.001); while significant moderate negative correlation was seen between vitamin D and HbA1c (r= -0.494, P= 0.001) and weak negative correlation was seen with B. Urea (r= -0.2, P= 0.028). No statistically significant correlations detected between vitamin D and all of age, DM duration, and s. creatinine.Conclusion: Our data suggest a correlation between reduced levels of vitamin D3 and diabetes nephropathy and it may be a potential predictor for both the occurrence and severity of diabetic nephropathy